2010
DOI: 10.1016/j.neulet.2010.07.059
|View full text |Cite
|
Sign up to set email alerts
|

State-dependent sculpting of olfactory sensory neurons is attributed to sensory enrichment, odor deprivation, and aging

Abstract: Gene-targeted deletion of the predominant Shaker potassium channel, Kv1.3, in the mitral cells of the olfactory bulb, decreases the number of presynaptic, odorant receptor (OR)-identified olfactory sensory neurons (OSNs) in the main olfactory epithelium (MOE) and alters the nature of their postsynaptic connections to mitral cell targets. The current study examined whether OSN density was state-dependent by examining the impact of 1) odor enrichment, 2) sensory deprivation, and 3) aging upon the number of P2- o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 28 publications
5
42
0
Order By: Relevance
“…To fully understand the expression level/pattern changes of a single gene, it is essential to employ multiple, complementary approaches. By examining genetically labeled OSNs in P2-IRES-tauLaz mice, two groups reported that sensory deprivation significantly reduced the number of P2 cells [24], [46], which is confirmed by our in situ hybridization data. It is worth noting that both in situ hybridization and microarrays examine the mRNA expression, and more studies would be required to understand how OR protein expression is modulated.…”
Section: Discussionsupporting
confidence: 85%
“…To fully understand the expression level/pattern changes of a single gene, it is essential to employ multiple, complementary approaches. By examining genetically labeled OSNs in P2-IRES-tauLaz mice, two groups reported that sensory deprivation significantly reduced the number of P2 cells [24], [46], which is confirmed by our in situ hybridization data. It is worth noting that both in situ hybridization and microarrays examine the mRNA expression, and more studies would be required to understand how OR protein expression is modulated.…”
Section: Discussionsupporting
confidence: 85%
“…Because Kv1.3 is important in sensory neurons (Rivera et al, 2005;Cavallin et al, 2010;Gazula et al, 2010) and leukocyte physiology (Vicente et al, 2003;Cahalan and Chandy, 2009) we analyzed the di-acidic E483/484 in neurons and lymphocytes. Rat embryo hippocampal neurons and Jurkat T-lymphocytes were transfected with Kv1.3wt and Kv1.3(I483/484).…”
Section: Resultsmentioning
confidence: 99%
“…In this context, the Kv1.3 channel participates in the activity of sensory neurons and also controls the activation and proliferation of leukocytes (Vicente et al, 2003;Rivera et al, 2005;Cahalan and Chandy, 2009;Cavallin et al, 2010;Gazula et al, 2010). Therefore, Kv1.3 is considered to be a fundamental pharmacological target for diseases related to the nervous and immune systems (Koeberle and Schlichter, 2010;Villalonga et al, 2010;Conforti, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Custom microarrays, PCR and in situ analyses show individual variability in OR gene expression with peaks occurring between mouse postnatal day 14 and day 60, followed by steep declines for some receptors during aging [12,28,29]. Because the sensitivity of the sensory neurons that continue to express ORs in aged mice appears comparable to younger mice, it seems plausible that receptor copy number for individual cells is not affected during aging [30].…”
Section: Olfactory Epithelium – Sensory Inputmentioning
confidence: 99%